Minors Lack the Autonomy to Consent to Gender-Affirming Care: Best Interests Must Be Primary - Bester, Johan C. (The Hastings Center report, 2024)
What ethically justifies the provision of invasive and irreversible treatments to minors? In this commentary, I examine this question in response to Moti Gorin's article “What Is the Aim of Pediatric ‘Gender-Affirming’ Care?,” which critiques autonomy-based arguments for justification of gender-affirming care in minors. Minors generally lack sufficient autonomy to make significant medical decisions or major life decisions. For this reason, parents are generally their decision-makers, working with medical professionals to choose treatments that serve the best interests of the minor. Medical care in minors is justified by beneficence, not autonomy, and this should be no different for gender-affirming care. This severely undermines autonomy-based arguments for provision of gender-affirming care to minors. Given the lack of conclusive evidence for benefit, the nature of the treatment, and the fact that gender dysphoria in minors resolves spontaneously in most cases, there is presently insufficient justification for provision of such care to minors.